THE EFFECT OF LYSINE AND METHIONINE AMINO ACID ON THE PERCENTAGE OF CARCASS AND COMMERCIAL CARCASES PIECES OF BROILER AGE OF 32 DAYS - I P. G. A. J., Saputra; Astawa, I P. A.; Sudiastra, I. W. (Jurnal Peternakan Tropika; Vol 9 No 3 (2021): Vol. 9 No. 3 Tahun 2021; September - December, 2021)
This study aimed to determine the effect of giving lysine and methionine amino acid through drinking water on carcass and commercial carcass pieces of broiler age of 32 weeks. It was conducted in the cage owned by Mr. I Made Arcana located in Candikusma Village, Jembrana for 32 days. This research was conducted using a completely randomized design (CRD) consisting of four treatments and four replications and in each replication used 12 heads of DOC CP 707 with an average body weight of 49.27 ± 0.90g. The treatments were : P0 = broiler without lysine and methionine amino acids in drinking water, P1 = broiler that given 0.02% lysine and methionine amino acid in drinking water, P2 = broiler that given 0.025% lysine and methionine amino acids in drinking water, and P3 = broiler that given 0.03% lysine and methionine amino acids in drinking water . The variables observed were slaughter weight, carcass weight, carcass percentage and the percentage of breast, wing, upper thigh, and lower thigh. The results showed that the treatments of P1, P2, and P3 could increase slaughter weight, carcass weight, carcass percentage and wing percentage, statistically significantly different (P<0.05). While the percentage of the chest, upper thigh, lower thigh and back statistically were not significantly different (P>0.05). Based on the results of the study, it can be concluded that the administration of 0.02 - 0.03% lysine and methionine amino acids in drinking water can increase slaughter weight, carcass weight, carcass percentage, and wing percentage, but not significantly effect on the percentage of breast, upper thigh, lower thigh, and back of broilers aged of 32 days.   Key words: broiler, amnino acid, lysine and methionine, carcass, percentage of                    carcass